TINDAKAN SUAMI DALAM MENGURANGI RASA NYERI PERSALINAN KALA SATU DI KLINIK MANDA JALAN KARYA CLINCING KECAMATAN MEDAN BARAT TAHUN 2017 - Lia Rosa Veronika Sinaga (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2017)
Labor is a process of expenditure (birth) the result of conception that can live outside the uterus through the vagina to the outside world. The process is said to be normal or spontaneous if the born baby is in a position behind the head and takes place without the help of relief devices, and does not hurt the mother and baby. This process generally takes place in less than 24 hours. The actions of husbands in reducing labor pain include massage, relaxation, imagination. This study uses a quantitative approach, with cross sectional study in which data regarding the independent and dependent variables were collected simultaneously which aims to find the husband of action in relieving pain during labor on road works alley clinics celincing manda subdistrict helvetia field in 2017. The population in this study is all the husbands who came to the maternity clinic accompanied her husband by Consecutive Sampling counted 38 respondents. This data was obtained from observation or observation of 20 questionnaires of respondents consisting of 10 massage measures, 5 relaxation action questionnaires, 5 questionnaire actions of imagination. The data obtained are processed by frequency distribution and analyzed descriptively with Cross Sectional approach, based on 36-45 years old majority 22 respondents (57,1%), high school education 22 respondents (60,1%), job of Karyawan 15 respondents (39.5%), based on Masase 22 Respondents (57.9%), 25 Respondents (65,7%) Relaxation, and Imagination 20 Respondents (52,6%). For the husband with this research is expected to add insight into the actions of husbands in reducing pain during childbirth such as massage, relaxation, imagination. For health care workers to teach the husband how to massage, relaxation, imagination by way of counseling so that husbands can perform these actions in reducing the pain of labor For the institution, this study is expected to be input and learning resources to students and useful for further research.